2012
DOI: 10.1177/0009922812440840
|View full text |Cite
|
Sign up to set email alerts
|

Early Pediatric Emergency Department Return Visits

Abstract: Among children who are discharged from the emergency department and return within 72 hours, most caregivers are satisfied with the care and instructions provided on their first visits. Though most patients have a PMD, many do not call them prior to their return ED visit, and those who do either cannot schedule an appointment or are told to return to the ED. The majority of patients return for clinical progression of illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
64
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 27 publications
5
64
0
1
Order By: Relevance
“…Our 7.5% 7-day ED revisit rate was greater than, although still within range of, previous ED revisit studies in North America. 3,[27][28][29] This result likely reflects the longer time period used to include revisits, rather than the frequently used 72-hour revisit window. The greatest patient-level predictors for revisiting an ED were age socioeconomic status and predilection for using an ED in the preceding year, which have been reported previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our 7.5% 7-day ED revisit rate was greater than, although still within range of, previous ED revisit studies in North America. 3,[27][28][29] This result likely reflects the longer time period used to include revisits, rather than the frequently used 72-hour revisit window. The greatest patient-level predictors for revisiting an ED were age socioeconomic status and predilection for using an ED in the preceding year, which have been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…1,25,[27][28][29] There is limited previous literature on immigrants and hospitalization. One study from Spain showed immigrant women are more likely to be hospitalized compared with Spanish-born women.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that disease progression is the cause of most return visits in the PED 4 10. Progression of disease does not necessarily mean that the patients should be treated in the ED.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of return visits within 72 h reported previously has ranged from 2.7% to 5.2% in the paediatric ED (PED)1 3 8 10 and 1.4–5.5% in the adult ED 7 9 11. Most studies of return visits have shown only characteristics of and factors related to return visits 1–3 5 12.…”
Section: Introductionmentioning
confidence: 98%
“…5 In fact, when faced with immediate problems, parents and youth seek emergency medical services prior to contacting their primary care physicians making the PED their first point of contact with the health care system. 7,13 Repeat presentations represent a large proportion of PED MH presentations with estimates ranging from 12% to 36%. [14][15][16] This may be the result of a lack of availability or difficulty accessing MH services that effectively meet this patient population's needs.…”
Section: Introductionmentioning
confidence: 99%